2014
DOI: 10.1080/07347332.2014.936649
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Pilot Study of Psychosocial Functioning in Head and Neck Cancer Patient–Caregiver Dyads

Abstract: This study explored the psychosocial functioning of 10 head and neck cancer patient-caregiver dyads over the radiation/chemoradiation (radiation or combined chemoradiation) treatment period, including the interdependence in patient-caregiver quality of life (QOL). Dyads were recruited prior to or at the initiation of radiation/chemoradiation treatment. Patient QOL decreased across the treatment trajectory, and many caregiver QOL subscales decreased during the middle of treatment. Caregiver burden increased ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Specifically, they: (1) are a convenient on-demand resource; (2) offer features to protect the anonymity of the user; (3) connect people through message boards and other interactive features for social support and information; (4) provide interactive features like videotaped sequences to demonstrate and reinforce behaviours that need to be acquired (e.g., regular practice of swallowing exercises); and (5) have greater reach to geographically dispersed populations like cancer survivors and their caregivers (Stull et al 2007). Given that the needs and experiences of cancer survivors and caregivers are interdependent (Nightingale et al 2014), IHCTs that provide information, support and skills training for the dyad (not just for the survivor) may facilitate coping with the physical and psychosocial side effects of illness. In turn, this could foster positive outcomes including better symptom management, faster rehabilitation and improved QOL for both the survivor and caregiver (Dubenske et al 2010).…”
Section: Use Of Interactive Health Communication Technologies May Facmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, they: (1) are a convenient on-demand resource; (2) offer features to protect the anonymity of the user; (3) connect people through message boards and other interactive features for social support and information; (4) provide interactive features like videotaped sequences to demonstrate and reinforce behaviours that need to be acquired (e.g., regular practice of swallowing exercises); and (5) have greater reach to geographically dispersed populations like cancer survivors and their caregivers (Stull et al 2007). Given that the needs and experiences of cancer survivors and caregivers are interdependent (Nightingale et al 2014), IHCTs that provide information, support and skills training for the dyad (not just for the survivor) may facilitate coping with the physical and psychosocial side effects of illness. In turn, this could foster positive outcomes including better symptom management, faster rehabilitation and improved QOL for both the survivor and caregiver (Dubenske et al 2010).…”
Section: Use Of Interactive Health Communication Technologies May Facmentioning
confidence: 99%
“…Given that the needs and experiences of cancer survivors and caregivers are interdependent (Nightingale et al . ), IHCTs that provide information, support and skills training for the dyad (not just for the survivor) may facilitate coping with the physical and psychosocial side effects of illness. In turn, this could foster positive outcomes including better symptom management, faster rehabilitation and improved QOL for both the survivor and caregiver (Dubenske et al .…”
Section: Introductionmentioning
confidence: 99%
“…Another strength of the present study was the evaluation of both caregiver and care recipient factors that might contribute to the caregiver’s cortisol response. Prior research has demonstrated interdependence among HNC patient and caregiver psychosocial factors (Nightingale et al, 2014; Patterson, Rapley, Carding, Wilson, & McColl, 2013). The present study augments that literature by also demonstrating a relationship between the care recipient’s QOL and the caregiver’s cortisol response.…”
Section: Discussionmentioning
confidence: 99%
“…Drabe and colleagues (2008) reported that HNC caregivers experience a high prevalence of psychiatric disorders, particularly agoraphobia (22.6%), and other studies have reported greater psychological distress and poorer psychological well-being in HNC caregivers in comparison to the general population (Ross, Mosher, Ronis-Tobin, Hermele, & Ostroff, 2010). Further, studies have also demonstrated that psychological distress and caregiver burden increase during the care recipient’s oncologic treatment for HNC (Badr, Gupta, Sikora, & Posner, 2014; Nightingale, Lagorio, & Carnaby, 2014). Collectively, these findings suggest an increased risk for a negative psychosocial sequela associated with the role of informal caregiving for HNC patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation